Gerschgorin disk theorem based spectrum sensing for wideband cognitive radio - Bin SHEN; Shu WANG; Qiong HUANG; Qian-bin CHEN (Tongxin xuebao)
Gerschgorin disk theorem (GDT) based wideband spectrum sensing methods, namely Gerschgorin likelihood estimate(GLE) algorithm and Gerschgorin disk radii iteration(GDRI) algorithm, were proposed for cognitive radios. By means of exploring the possibility of utilizing GDT in wideband spectrum sensing, the occupied and the idle licensed subbands was distingwished by respectively identifying the cardinalities of the corresponding subband sets. With an aim to strengthen the performance of GLE and GDRI, a subband continuity based wideband sensing algorithm was further proposed. Simulation results show that GLE sensing performance remains consistent when the SNR is low, whereas GDRI requires no a priori knowledge of the noise power and the PU signal and it overcomes the practical problem of small spectrum observation samples. With salient performance and practical feasibility, the proposed GLE and GDRI may serve as candidate wideband sensing technologies for cognitive radios.